Pengaruh media Kirana berbasis augmented reality terhadap kompetensi profesional calon guru SD di bidang seni tari - Dwi Anggraini; Yuli Amaliyah; Muhammad Habib Ramadhani (Tunas Nusantara, 2026)
This study aims to determine the effect of Kirana media based on Augmented Reality to improve the professional competence of prospective elementary school teachers in the field of dance. The type of research used is quantitative with the experimental method of the matching only pretest posttest control group design. The study population was all students of the Elementary School Teacher Education Study Program, JIP, FKIP, Bengkulu University, Semester III who took the Dance Arts Education in Elementary School course. The research sample after being randomized was students in semester III of class B and C. The data were analyzed using descriptive analysis techniques using SPSS version 24. Prerequisite tests were also carried out, namely the normality test, homogeneity test, and the Man Whitney U test. The results of the study showed that the results of the Man Whitney U test showed that the asymp value of Sig. (2-tailed) was 0.003 <0.05. Thus, it can be concluded that there is an influence of Kirana media based on Augmented Reality on the professional competence of prospective elementary school teachers in the field of dance